Xenon as an Adjuvant to Propofol Anesthesia in Patients Undergoing Off-Pump Coronary Artery Bypass Graft Surgery: A Pragmatic Randomized Controlled Clinical Trial. (October 2017) - Al tmimi, Layth; Devroe, Sarah; Dewinter, Geertrui; Van de Velde, Marc; Poortmans, Gert; Meyns, Bart; Meuris, Bart; Coburn, Mark; Rex, Steffen
Abstract : BACKGROUND: Xenon was shown to cause less hemodynamic instability and reduce vasopressor needs during off-pump coronary artery bypass (OPCAB) surgery when compared with conventionally used anesthetics. As xenon exerts its organ protective properties even in subanesthetic concentrations, we hypothesized that in patients undergoing OPCAB surgery, 30% xenon added to general anesthesia with propofol results in superior hemodynamic stability when compared to anesthesia with propofol alone. METHODS: Fifty patients undergoing elective OPCAB surgery were randomized to receive general anesthesia with 30% xenon adjuvant to a target-controlled infusion of propofol or with propofol alone. The primary end point was the total intraoperative dose of norepinephrine required to maintain an intraoperative mean arterial pressure >70 mm Hg. Secondary outcomes included the perioperative cardiorespiratory profile and the incidence of adverse and serious adverse events. RESULTS: Adding xenon to propofol anesthesia resulted in a significant reduction of norepinephrine required to attain the predefined hemodynamic goals (cumulative intraoperative dose: median [interquartile range]: 370 [116–570] vs 840 [335–1710] µg, P = .001). In the xenon-propofol group, significantly less propofol was required to obtain a similar depth of anesthesia as judged by clinical signs and the bispectral index (propofol effect site concentration [mean ± SD]: 1.8 ± 0.5 vs 2.8 ± 0.3 mg, P ⩽ .0001). Moreover, the xenon-propofol group required significantly less norepinephrine during the first 24 hours on the intensive care unit (median [interquartile range]: 1.5 [0.1–7] vs 5 [2–8] mg, P = .048). Other outcomes and safety parameters were similar in both groups. CONCLUSIONS: Thirty percent xenon added to propofol anesthesia improves hemodynamic stability by decreasing norepinephrine requirements in patients undergoing OPCAB surgery. Abstract : Supplemental Digital Content is available in the text.Published ahead of print June 8, 2017.